Three-dimensional reconstruction of the feeding apparatus of the tick Ixodes ricinus (Acari: Ixodidae): a new insight into the mechanism of blood-feeding - Vancová, Marie; Bílý, Tomáš; Šimo, Ladislav; Touš, Jan; Horodyský, Petr; Růžek, Daniel; Novobilský, Adam; Salát, Jiří; Strnad, Martin; Sonenshine, Daniel E; Grubhoffer, Libor; Nebesářová, Jana (Scientific reports, 2020)
The different components of the mouthparts of hard ticks (Ixodidae) enable these parasites to penetrate host skin, secrete saliva, embed, and suck blood. Moreover, the tick's mouthparts represent a key route for saliva-assisted pathogen transmission as well as pathogen acquisition from blood meal during the tick feeding process. Much has been learned about the basic anatomy of the tick's mouthparts and in the broad outlines of how they function in previous studies. However, the precise mechanics of these functions are little understood. Here, we propose for the first time an animated model of the orchestration of the tick mouthparts and associated structures during blood meal acquisition and salivation. These two actions are known to alternate during tick engorgement. Specifically, our attention has been paid to the mechanism underlining the blood meal uptake into the pharynx through the mouth and how ticks prevent mixing the uptaken blood with secreted saliva. We animated function of muscles attached to the salivarium and their possible opening /closing of the salivarium, with a plausible explanation of the movement of saliva within the salivarium and massive outpouring of saliva.
Keywords: Microscopy, Electron, Scanning; zvířata; Salivation; Imaging, Three-Dimensional; ústa; myši; Mice; salivace; Tick Infestations; stravovací zvyklosti; klíště; zobrazování trojrozměrné; Nymph; mikroskopie elektronová rastrovací; Animals; Female; Feeding Behavior; Ixodes; ženské pohlaví; infestace klíšťaty; nymfa; Mouth